Kardiochirurgia dorosłych Polish ventricular assist device (POLVAD) support for the treatment of cardiogenic shock in patients with myocarditis - Litwiński, Paweł; Woźniewicz, Bogdan; Religa, Grzegorz; Pastuszek, Małgorzata; Parulski, Adam; Jasińska, Małgorzata; Kocańda, Szymon; Kustosz, Roman; Siondalski, Piotr; Religa, Zbigniew (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2005)
ventricular assist device, POLVAD, myocarditis, cardiogenic shock